A Phase 1 and pharmacokinetic study evaluating daily or weekly schedules of the humanized anti-GD2 antibody hu14.18K322A in recurrent/refractory solid tumors. Issue 1 (1st January 2020) - Bishop, Michael W.; Hutson, Paul R.; Hank, Jacquelyn A.; Sondel, Paul M.; Furman, Wayne L.; Meagher, Michael M.; Navid, Fariba; Santana, Victor M.
ABSTRACT: Hu14.18K322A is a humanized anti-GD2 monoclonal antibody with a single point mutation that reduces complement-mediated cytotoxicity, with a maximum tolerated dose (MTD) of 60 mg/m 2 daily for 4 days in children with recurrent/refractory neuroblastoma. We report additional results of a Phase 1 trial to determine the MTD and safety profile of hu14.18K322A in patients with osteosarcoma, and of an alternative schedule of weekly hu14.18K322A administration in patients with neuroblastoma or osteosarcoma. Eligible patients with recurrent/refractory osteosarcoma received hu14.13K22A daily x4 every 28 days in a Phase 1 traditional 3 + 3 dose escalation design. Additional patients with osteosarcoma were then enrolled to receive hu14.18K322A once weekly for 4 weeks per course. Patients with recurrent/refractory neuroblastoma were also enrolled on the weekly schedule at 50 mg/m 2 /dose. Six patients with osteosarcoma treated on the daily schedule received a median of 2 (range 1–6) courses; the recommended daily dose was established as 60 mg/m 2 . Three patients had stable disease (SD) as best overall response. Five patients (3 neuroblastoma, 2 osteosarcoma) enrolled on the weekly schedule received a median of 1 (1–3) course; 2 achieved SD as best overall response. Pain, fever, hematologic toxicities, hyponatremia, and ocular/visual abnormalities were common toxicities among both schedules. Dose-limiting toxicities attributed to hu14.18K322A included anorexia and fatigue (n = 1). Pharmacokinetic profiles were similar between daily and weekly schedules. The recommended dose for patients with osteosarcoma receiving daily hu14.18K322A x4 is 60 mg/m 2 . Patients receiving the weekly schedule experienced similar pharmacokinetics and toxicity profile as the daily schedule.